Psychiatry postgraduate training in Malaysia : guide for applications - Zainal, Nor Zuraida; Gill, Jesjeet Singh; Nik Jaafar, Nik Ruzyanei; Baharudin, Azlin; Ohnmar Naing, Noorjan @ Khin; Kiat, Ang Jin; Ibrahim, Normala; Yasin, Mohd Azhar; Husain, Maruzairi; Yusoff, Eizwan Hamdie; Razali, Salmi; Silim, Ummi Adzlin; et al. (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia MERDU, Fakulti Perubatan, Universiti Malaya, 50603 Kuala Lumpur, Malaysia npmcmy@gmail.com, 2021)
This document is a guide for those applying to enter postgraduate training in psychiatry. It informs potential applicants of the entry requirements through a series of extracts from the National Postgraduate Curriculum in Psychiatry. The curriculum will be implemented after it is approved by the Malaysian Medical Council.